Stress Analysis Of The Human Tibia Knee Joint Using Finite Element Method - Mohamed Azmin, Nor Fadhillah (2007)

(untitled)
Despite the several years of studies that have been contributed to the human knee joint in pursue of producing a failure free knee joint protheses, there are still a lot of rooms for improvement on the available prostheses. In this present study, a series of analyses on the human tibia has been carried out. The objectives of the present study were to study effects of stress distribution on human tibia in various degrees of flexion simulating walking and squatting. The Finite Element (FE) method was adopted for the analysis. Through the finite element analyses, data concerning the stress distribution and von Misses stress during gait cycle and squatting were obtained. The results obtained were compared with those of the experimental literature for validation. The results of this present study indicated that low stress value occurs during toe-off simulation while the high stress value occurs during deep flexion with the knee is flexed 90°. The von Mises stress observed on the medial compartment during these instants were 13.85MPa and 26.84MPa respectively. The obtained average stress distribution of a gait cycle and deep flexions were 15.29MPa and 25.09MPa respectively. it is worth to note that a high stress concentration occurs at the tibial plateau, distinctively at the medial compartment. This implies that under deep flexion a possible unstable fracture will be initiated since the maximum stress allowable on the tibia is 25MPa. In conclusion, this kind of research gives a better understanding of the stress applied on the tibia by body weight that assist on designing Total Knee Replacement against failure. The result could support in the context of minimizing contact stress between the tibia bone and the tibial insert